COMPARATIVE ANALYSIS OF THE OUTCOMES OF CONTINUOUS AND BOLUS ADMINISTRATION OF SEDATIVES IN CHILDREN UNDERGOING MECHANICAL VENTILATION (Herald of the National Children's Medical Center, 2025)
Adequate sedation is an essential component of the management of children on mechanical ventilation. The optimal regimen of sedation remains a matter of debate. Continuous infusion ensures a stable concentration of the drug in the blood and can reduce the risk of desynchronization with the respirator, however, it is associated with the development of tolerance and withdrawal syndrome. Bolus administration reduces the cumulative dose of drugs, but may be accompanied by periodic discomfort and anxiety of the patient.
Keywords: sedation; children; ventilator; midazolam; fentanyl; bolus; infusion; withdrawal syndrome